Coordinating distributed autonomous agents with a real-time database: the CAMBADA project - Almeida, Luís (2004)
Interest on using mobile autonomous agents has been growing, recently, due to their capacity to cooperate for diverse purposes, from rescue to demining and security. However, such cooperation requires the exchange of state data that is time sensitive and thus, applications should be aware of data temporal coherency. In this paper we describe the architecture of the agents that constitute the CAMBADA robotic soccer team developed at the University of Aveiro, Portugal. This architecture is built around a real-time database that is partially replicated in all team members and contains both local and remote state variables. The temporal coherency of the data is enforced by an adequate management system that refreshes each database item transparently at a rate specified by the application. The application software accesses the state variables of all agents with local operations, only, delivering both value and temporal coherency.